The Effectiveness of a Play-Based Training Programme in Reducing Aggressive Behaviour in Intellectually Disabled Children Capable of Learning - Al-Dhuwaibi, Asmaa Omran; Abdel Samie, Moufida Abdel Salam; Al-Dhafeer, Huda Ali; Qusayl, Khawla Misbah (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This research aimed to identify the effectiveness of a play-based training program in reducing aggressive behavior among mentally handicapped children who can learn, to achieve this, the experimental approach was used so that the research was applied to a sample of mentally handicapped children who can learn at the Center for Racking Pens inside the city of Zliten, and where the sample was limited to children who have the problem of aggressive behavior, which numbered (6) children aged (6-10) years were selected intentionally, where the sample was divided To two control groups and an experimental one and used the scale of aggressive behavior of children for pre, post and tracking measurement of the application of the program. The results of the research found that the relative weight of the research sample reached (62.45%) before the application of the program and this indicates a level higher than the average in aggressive behavior and that the relative weight of the research sample reached (41.46%) after the application of the program and this indicates a level lower than the average in aggressive behavior, as well as the relative weight of the research sample reached (39.48%) after the application of the tracking scale of the program and this indicates a level lower than the average in aggressive behavior, and that there are no statistically significant differences.